PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP KEANDALAN LAPORAN KEUANGAN DENGAN MEDIASI PENATAUSAHAAN ASET TETAP - Trisnani, Emy Dwi; Dimyati, Mohamad; Paramu, Hadi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: This study aims to analyze the influence of Internal Control System (SPI) on the reliability of financial statements, with fixed assets administration as the intervening variable, in the Government of Bondowoso Regency. Data were analyzed by using Structural Equation Modeling (SEM). Results shows that Internal Control System has a significant positive effect on the reliability of financial statements and fixed assets administration, fixed assets administration has a significant positive effect on the reliability of financial statements, and the fixed assets administration has a significant role in mediating the effect of Internal Control System on the reliability of financial statements. Keywords: SPI, Administration of Fixed Assets, Financial Statements Reliability.